RELIABILITY OF THE SIMPLE 20-MINUTE WHOLE-BLOOD CLOTTING TEST (WBCT20) AS AN INDICATOR OF LOW PLASMA-FIBRINOGEN CONCENTRATION IN PATIENTS ENVENOMED BY BOTHROPS SNAKES - Sanomartins, I; Fan, H; Castro, S; Tomy, S; Franca, F; Jorge, M; Kamiguti, A; Warrell, D; Theakston, R; Cardoso, J; Leite, R; Nishioka, S; et al. (1994)
A simple whole blood clotting test (WBCT20) was assessed for its efficacy in determination of severe defibrinogenation in patients envenomed by Bothrops snakes in Brazil. There was a close relationship between the results of the WBCT20 and plasma fibrinogen levels in 69 moderately envenomed patients. The advantage of the WBCT20 over estimation of plasma fibrinogen concentrations in patients is that it is a simpler, faster and more reliable test. It is also of use in assessing the effectiveness of antivenom therapy in relation to the restoration of blood coagulability. © 1994.